Conservation Options for Private Landowners in Florida - Martin B. Main; Annisa Karim; Mark E. Hostetler (EDIS)
The objective of this document is to explain the principal land conservation options available to landowners and to provide contact information for organizations in Florida that partner in these efforts. Actual contact and negotiated agreements are left to the landowners, their legal and financial advisors, and the partner organizations. This document, Circular 1441, is one of a series of the Department of Wildlife Ecology and Conservation, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Original publication date: April 2003.